PENGEMBANGAN MEDIA PEMBELAJARAN ARITMATIKA SOSIAL BERBASIS ROLE PLAYING GAME BERBANTUAN MACROMEDIA FLASH PROFESSIONAL 8 - Nur Saidah; Dita Riska Nurputri; Nani Ratnaningsih (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the feasibility of using mathematics learning media in-based Social Arithmetic materials Role Playing Game with the help of theapplication Macromedia Flash Professional 8. The method used in this study is themethod Research and Development using the ADDIE development procedure (Analysis, Design, Development, Implementation, and Evaluation). Methods of data collection using questionnaires, interviews, and expert validation. The results of data analysis in the media validation process include media experts, namely 4.83 meaning